المسائل العقدية في معجم مقاييس اللغة لابن فارس: جمعا وعرضا - الحمد، محمد بن إبراهيم بن أحمد (جامعة القصيم, 2021)
يعد ابن فارس من أكابر علماء العربية، ويعد بحثه معجم مقاييس اللغة أعظم كتبه، ومن أهم المعاجم العربية، على الإطلاق. وقد احتوى على علوم شتى، ومباحث متنوعة، ومباحث متنوعة مبثوثة في غضون دراسته لأصول الألفاظ ومقاييسها. هذا البحث يدور حول ما تضمنه ذلك الكتاب من المسائل العقدية سواء ما كان منها متعلقا بأركان الإيمان وأصول العقيدة، أو ما يلحق بذلك من مسائل.
Ibn Faris is considered one of the greatest Arabic Language scholars, and his compilation is considered one of the greatest lexicon in the Arabic language, his greatest book, and one of the most important Arabic lexicon ever. It contained various sciences, various investigations, and various investigations transmitted in the course of his study of the origins of words and their standards. This research revolves around what the book contains regarding the doctrinal aspects, whether it was related to the pillars of faith and the essentials of faith, or the issues attached thereto.
Keywords: اللغة العربية -- المعاجم اللغوية -- علم الدلالة -- المصطلحات التعبيرية -- المسائل العقدية -- ابن فارس، أحمد بن فارس بن زكرياء، ت. 395 هـ